Response to Growth and Results of Romaine Lettuce (Lactuca sativa Var. Longifolia) Plants on Some Dosage of Kasgot Pupuk with Different Planting Spaces - Intan Rohma Nurmalasari; Asrofi Rizal (Universitas Muhammadiyah Sidoarjo, 2024)
Romaine lettuce production has decreased on a national scale. One effort that can be made to increase the production and yield of romaine lettuce is to cultivate it with proper fertilization and reduce the use of inorganic fertilizers and pesticides. This research aims to determine the interaction of cassava fertilizer doses and differences in planting distance for the growth and yield of romaine lettuce plants. The method used is a factorial randomized block design (RAK) with treatments of 5 tons/ha, 10 tons/ha, 15 tons/ha, and 20 tons/ha. as well as differences in planting distances of 15x20cm, 20x25cm and 25x25cm. The results of the treatment of cassava fertilizer dosage and plant spacing had a significant effect on the research variables of leaf number, but had no effect on plant height, root volume, wet weight and dry weight.